Relevance or 'relevate'? How university business schools can add value through reflexively learning from strategic partnerships with business. Issue 3 (July 2014) - Paton, Steve; Chia, Robert; Burt, George
Much has been debated about the perceived relevance/irrelevance of business schools in addressing business needs with some suggesting that academic research is not applicable to practice. We contribute by claiming the debate is itself somewhat misplaced and the real task of business schools is to instil the art of 'relevating' the seemingly irrelevant in order to prepare managers for the challenges they face. Paradoxically, we contend that in relentlessly pursuing scholarship, academics can make a valuable contribution to practice by offering counterintuitive viewpoints that challenge business mindsets. Ironically, value-adding contributions to practice are best made when academia resists the seductive tendency to capitulate to the immediate demands of the client. For it is only by challenging conventional wisdom and expectations and thereby creating dissonance in the minds of managers, that new and unthought avenues of action may be opened up for consideration. We illustrate this by examining the experiences of a partnership between a multinational corporation and a university in the United Kingdom where the executive education programme was carried out using action learning techniques while encouraging reflexivity in practice.